Reflets discursifs des élites intellectuelles et culture classique à l’époque contemporaine - Constantin Bobas (Cahiers Balkaniques)
This paper proposes a reflection about the relationships between intellectual elites and ancient Greek culture, in particular in the contemporary era. While focusing on the Modern Greek cultural area it brings together approaches from other horizons in order to examine some of the processes by which these relationships function.